A redox mediator doped gel polymer as an electrolyte and separator for a high performance solid state supercapacitor. Issue 7 (21st February 2015) - Ma, Guofu; Dong, Miaomiao; Sun, Kanjun; Feng, Enke; Peng, Hui; Lei, Ziqiang
<x xml:space="preserve">Abstract</x> A stable and effective redox-mediator gel electrolyte has been prepared by doping indigo carmine (IC) into a polyvinyl alcohol sulfuric acid polymer system (PVA–H2SO4), and a high performance solid state supercapacitor is fabricated by utilizing activated carbon as electrodes and the prepared gel polymer (PVA–H2SO4–IC) as an electrolyte and separator.